1994
DOI: 10.1104/pp.105.1.191
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Use within the Growing Leaf Blade of Tall Fescue

Abstract: Leaf elongation rate (LER) of grasses depends on N supply and i s expressed mostly through cell production, whereas most N in mature leaf tissues is chloroplastic. Our objective was to evaluate a possible competition for N between cell production and chloroplast development processes, utilizing the gradient of cell development along the leaf growth zone of tal1 fescue (Festuca arundinacea Schreb.). Under the two contrasting N regimes, total N content was highest in the cell production zone, declined sharply as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
96
2
18

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(126 citation statements)
references
References 20 publications
10
96
2
18
Order By: Relevance
“…Other studies evaluating effects of N on leaf elongation rate also presented similar results (Gastal & Nelson, 1994;Alexandrino et al, 2000). According to Volenec & Nelson (1994), the increase in leaf elongation rate, caused by nitrogen fertilization is due to a greater cell production, with little effect on the final size of the cell or on epidermal cell elongation rate.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Other studies evaluating effects of N on leaf elongation rate also presented similar results (Gastal & Nelson, 1994;Alexandrino et al, 2000). According to Volenec & Nelson (1994), the increase in leaf elongation rate, caused by nitrogen fertilization is due to a greater cell production, with little effect on the final size of the cell or on epidermal cell elongation rate.…”
Section: Resultssupporting
confidence: 71%
“…Morphogenetic traits can be subdivided into: leaf appearance rate; leaf elongation rate and leaf senescence rate, in addition to stalk elongation for tropical grasses (Sbrissia & Da Silva, 2001). Leaf elongation rate of the grasses is very responsive to N fertilization (Gomide et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This was corroborated by the results of a concomitant experiment carried out in the same area involving measurements of morphogenetic responses to treatments imposed (Table 4). Gastal and Nelson (1994) commented that nitrogen can generate a three to four fold increase in leaf elongation rate (LER), suggesting that this is the main morphogenetic response to nitrogen fertiliser application. Although LER is the characteristic determining acceleration of the growth rhythm of plants, tiller population density (TPD) plays an important role in increasing herbage bulk density and herbage mass on nitrogen fertilised swards (Fagundes et al, 2006;Mesquita et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The leaf elongation rate and the length of the leaf growth zone (region where cell division and expansion occurs) exhibit negative correlations to leaf dry matter content (Arredondo and Schnyder 2003). Leaf nitrogen content is closely associated with N deposited during cell production (Gastal and Nelson 1994). Therefore, Pontes et al (2007) have suggested that N yield declines with N deposition per unit cell volume in the growth zone.…”
Section: Grass Strategies Along Nutrient Gradientsmentioning
confidence: 99%